La distribución de caramelos duros, rellenos y masticables producidos localmente para la ciudad de Quito - Cabrera Zambrano, Luis Andrés (2011)
The distribution of chewy, hard and fill candies in the city of Quito are handled with different distribution channels where the retail channel is ideal for this project in which the consumption of confectionery has greater demand. For that reason, was developed a plan of distribution where small and medium-sized enterprises that do not have the number of necessary products to develop their own distribution, can find a strategic partner that has the necessary and specialized structure in the distribution of candies for Quito.